Exploring the Covid-19 pandemic as a catalyst for stimulating future research agendas for managing crises and disasters at international sport events - Miles, L.; Shipway, R. (Virgina Tech, 2020)
While the interdisciplinary study of crisis, disaster, and emergency management has become increasingly sophisticated, the identification of synergies, useful concepts, and future research agendas in relation to studies within the domain of sport event management to inform these areas, is still at a very early stage of development. The far-reaching global impact of the COVID-19 pandemic further illustrates the timely importance of this research agenda for both sports events and broader studies in festivals and events. The purpose of this article is to critically scope the resilience landscape to help further understand how studies on both international sports events (ISEs) specifically, and both sport and event management studies more generally, could be better informed by disaster management and resilience studies. The article highlights eight key thematic areas that merits further investigation and combines to identify a multidisciplinary research agenda and framework for advancing knowledge on managing crises and disasters in both sport and event management studies.